Flow diversion covering the M1 origin as a last resort. Issue 3 (19th December 2018) - Lin, Li-Mei; Bender, Matthew T; Colby, Geoffrey P; Jiang, Bowen; Campos, Jessica K; Zarrin, David A; Young, Robert W C; Xu, Risheng; Caplan, Justin M; Huang, Judy; Tamargo, Rafael J; Coon, Alexander L
Abstract : Introduction: Internal carotid artery termination (ICAT) and proximal A1 aneurysms can be challenging for open surgical clipping or endovascular coiling. Treatment with flow diversion covering the middle cerebral artery (MCA), an end vessel supplying a terminal circulation, has not been reported. Methods: A prospective, Institutional Review Board-approved database was analysed for patients with pipeline embolisation device (PED) placement from the anterior cerebral artery (ACA) to the ICA during cerebral aneurysm treatment. Results: Nine cases were identified, including five proximal A1, three posterior communicating artery and one ICAT aneurysm locations. Average aneurysm size was 8.3 mm (range 3–17), with 67% saccular and 78% right-sided. Primary indication for treatment was significant dome irregularity (44%), recurrence or enlargement (33%), underlying collagen vascular disorder (11%) and traumatic pseudoaneurysm (11%). Preservation of the ipsilateral ACA (with PED placed in A1) was performed when the anterior communicating artery (67%) or contralateral A1 (33%) were absent on angiography. Adjunctive coiling was done in four cases (44%). There was one major stroke leading to mortality (11%) and one minor stroke (11%). Clinical follow-up was 27 months on average. Follow-up digital subtraction angiography (average interval 15 months) showed complete aneurysm obliteration (88%) or dome occlusion with entry remnant (12%). The jailed MCA showed minimal or mild delay (primarily anterograde flow) in 75% of cases and significant delay (reliance primarily on ACA and external carotid artery collaterals) in 25%. Conclusions: Covering the MCA with a flow diverting stent should be reserved for select rare cases. Strict attention to blood pressure augmentation during the periprocedural period is necessary to minimise potential ischaemic compromise.